Co-expression of lung alveolar epithelial type I and II cell-selective proteins in response to injury - Clegg, Gareth Roger. (The University of Edinburgh, 2007)
The internal surface of the lung is covered by alveolar epithelial type I (ATI) and II (ATII) cells. In response to injury ATII cells proliferate and transdifferentiate to ATI cells. Currently, there are no simple methods to identify transdifferentiation in vivo. This study used a novel combination of ATI and ATII cell-selective antibodies to investigate the phenotype of the alveolar epithelium following Staphylococcus aureusinduced 'direct' lung injury. Imaging using confocal laser scanning microscopy with 2D and 3D image analysis allowed qualitative and quantitative investigation of the epithelial response to injury. Following distal airway instillation of S. aureus, the alveolar epithelium was covered with ATII cells (MMC4/RTII₇₀-positive cells) and ATI cells (RTI₄₀-positive cells) as seen in control lungs. However, the surface area covered by ATII cells was significantly increased, while the surface area covered by ATI cells was significantly decreased, in comparison with controls. Ultrastructural studies confirmed the decrease in ATI cell numbers following S. aMrews-inoculation. The alveolar wall of S. awrews-injured lungs also contained cells that co-stained with a unique combination of ATI and ATII cell proteins, RTI₄₀ and MMC4. To determine whether RTI₄₀/MMC4-positive cells were likely to be intermediates in the transition of ATII to ATI cells I examined ATII cells as they transformed to ATI-like cells in culture (day 0 to 5). Only cells on day 1 of culture were RTI₄₀/MMX^l positive. I also examined the developing lung for RTI₄₀/MMCd positive cells. Co-staining cells were not found in the developing alveolar epithelium, but they were present in small airways. I also developed a rat model of haemorrhagic shock induced 'indirect' alveolar epithelial injury as a platform for future work. Here I have developed a robust technique for imaging ATII cell transdifferentiation in vivo and in vitro. This work has identified a novel alveolar epithelial phenotype, RTI₄₀/MMC4, in repairing lungs and in ATII cells as they transdifferentiate to ATI-like cells in vitro. These data suggest that RTI₄₀/MMC4-positive cells can be used to both visualize alveolar epithelial intermediates in vivo and to investigate the regulation of ATII cell transdifferentiation following injury.